Empowering Communities through Citizen Science: Dengue Prevention in Córdoba - Estallo, Elizabet Lilia (2024)
Traditional mosquito vector control methods have proved ineffective in controlling the spread of dengue fever. This study aimed to assess the effectiveness of community engagement through student-led science in promoting dengue prevention and socioecological factors in the temperate urban city of Córdoba, Argentina. It assesses community perceptions, knowledge, attitudes, and preventive practices regarding dengue fever and its vector. Results showed a significant increase in knowledge about the vector and the disease and respondents’ adoption of good preventive practices. Student-led science was identified as a valuable tool for reaching households and leading to behavior changes at home. Furthermore, the findings highlighted the need for school programs to address vector biology and vector-borne disease prevention all year round. This study provides invaluable insights into the effectiveness of community engagement through student-led science to promote dengue prevention and socioecological factors. The findings suggest that this approach could be used to control the spread in other regions affected by the disease.